SCHENGEN BORDERS CODE IN THE ASPECT OF BORDER SECURITY - Gaveika, Artūrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Latvia has joined the Schengen area in 2007 and has already passed three Schengen evaluations. The aim of the article is to analyse the Schengen Borders Code in the context of border security.  Based on analysis of the Schengen Borders Code implementation in Latvia the author develops and puts forward suggestions on Schengen Borders Code content improvement as well as  its judicial systematisation development. The research tasks include the investigation of the current EU and national normative regulations, legal practices, the conclusions of Latvian and foreign law researchers by using analytical, historical and comparative methods.The improvement of the national normative regulation was started long before Latvia's accession to the Schengen area. In 2006, the Schengen Borders Code entered into force, which was revised due to the migration crisis in the Mediterranean region and adopted in 2016 in an improved version. The further development of the Schengen Borders Code is important from the point of view of the right to free movement of persons and from the point of view of ensuring public security in the face of today's challenges related to terrorism, international crime, uncontrolled migration and the spread of disease.The main achievement of the research is that the author has defined the main areas of Schengen Borders Code further development.